2017
DOI: 10.15252/embj.201695223
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and positioning determine the specific role of the XPFERCC 1 endonuclease in interstrand crosslink repair

Abstract: XPF‐ERCC1 is a structure‐specific endonuclease pivotal for several DNA repair pathways and, when mutated, can cause multiple diseases. Although the disease‐specific mutations are thought to affect different DNA repair pathways, the molecular basis for this is unknown. Here we examine the function of XPF‐ERCC1 in DNA interstrand crosslink (ICL) repair. We used Xenopus egg extracts to measure both ICL and nucleotide excision repair, and we identified mutations that are specifically defective in ICL repair. One o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 47 publications
6
61
0
Order By: Relevance
“…Furthermore, the Xenopus cell-free replication-coupled repair system demonstrated that ICL unhooking is abolished when XPF is immunodepleted, but not MUS81 or FAN1 (Klein Douwel et al, 2014). Additionally, in vitro reconstitution assays have shown that XPF-ERCC1 alone is able to perform dual incisions flanking an ICL located near the ssDNA/dsDNA junction of a splayed arm "forklike" (simple fork) DNA substrate, or in conjunction with the nuclease scaffold protein SLX4 (Kuraoka et al, 2000;Hodskinson et al, 2014;Klein Douwel et al, 2014), where SLX4 plays a key role in recruiting and positioning XPF-ERCC1 for incision (Klein Douwel et al, 2017). Finally, in the context of double-stranded DNA substrates, XPF-ERCC1 has been reported to act in an 3 0 -to-5 0 exonuclease-like fashion, digesting past a site-specific ICL (Mu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Xenopus cell-free replication-coupled repair system demonstrated that ICL unhooking is abolished when XPF is immunodepleted, but not MUS81 or FAN1 (Klein Douwel et al, 2014). Additionally, in vitro reconstitution assays have shown that XPF-ERCC1 alone is able to perform dual incisions flanking an ICL located near the ssDNA/dsDNA junction of a splayed arm "forklike" (simple fork) DNA substrate, or in conjunction with the nuclease scaffold protein SLX4 (Kuraoka et al, 2000;Hodskinson et al, 2014;Klein Douwel et al, 2014), where SLX4 plays a key role in recruiting and positioning XPF-ERCC1 for incision (Klein Douwel et al, 2017). Finally, in the context of double-stranded DNA substrates, XPF-ERCC1 has been reported to act in an 3 0 -to-5 0 exonuclease-like fashion, digesting past a site-specific ICL (Mu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In this context XPF-ERCC1 nicks the damaged DNA strand 5′ of the lesion at the ds/ss junction of an NER repair bubble. It is also required for interstrand cross-link repair (ICLR), some double-stranded break repair processes, base excision repair, Holliday junction resolution, gene-conversion and telomere maintenance [4][5][6][7][8][9][10] . Mutations in XPF and ERCC1 genes are associated with genetic disorders exhibiting diverse phenotypes.…”
mentioning
confidence: 99%
“…Incision assay was performed as described previously (Klein Douwel et al, 2014; 2017). Briefly, pICL (225 ng) and pQuant (11.3 ng) were incubated with 1.5 units NB-BSR DI enzyme (NEB) in 1× NEBuffer 2.1 for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%